THE EFFECT OF CHRISTIAN TEACHERS ON MULTICULTURAL PROBLEMS: A Descriptive Quantitative on the Student Effectiveness based on Luke 10:25-37 - Maria Titik Windarti; Sri Rezeki; Olis Olis; David Ming (Didache: Jurnal Teologi dan Pendidikan Kristen, 2022)
The main problem studied is how the multicultural problems faced by Christian teachers can be solved based on the teachings of the Bible, especially in luke 10:25-37. This research was conducted with the aim of identifying an overview of multicultural problems, as well as expressing views on multicultural education from both a general and Christian perspective and views on the role and duties of teachers. In addition, it aims to convey the message of the New Testament text, luke 10:25-37, in order to provide input for the teacher's constructive service to students. So that it can provide implications for multicultural services as a signification for Christian teachers. The method used in this study is descriptive analysis method, a research that seeks to describe by interpreting the consequences that are happening. While the type of research used is quantitative by conducting literature studies, studying the Bible text in luke 10:25-37, and field studies. In field research, researchers conducted participatory observations and interviews with teachers and students to obtain accurate data on existing problems so that appropriate solutions could be sought. The results of the research on the multicultural problem of teachers in Christian theology secondary schools in Bogor Regency based on cultural pluralism among students, it is proposed to teachers the following things: first, teachers need to increase knowledge about multicultural and multicultural education. Second, develop a creative attitude in learning. Third, multicultural appreciation is expressed in the Samaritan exemplary attitude in giving help without distinguishing who the person being helped is.